Post-feeding transcriptomics reveals essential genes expressed in the midgut of the desert locust - Van Lommel, Joachim; Holtof, Michiel; Tilleman, Laurentijn; Cools, Dorien; Vansteenkiste, Seppe; Polgun, Daria; Verdonck, Rik; Van Nieuwerburgh, Filip; Vanden Broeck, Jozef (Frontiers in Physiology, 2023)
The digestive tract constitutes an important interface between an animal’s internal and external environment. In insects, available gut transcriptome studies are mostly exploratory or look at changes upon infection or upon exposure to xenobiotics, mainly performed in species belonging to holometabolan orders, such as Diptera, Lepidoptera or Coleoptera. By contrast, studies focusing on gene expression changes after food uptake and during digestion are underrepresented. We have therefore compared the gene expression profiles in the midgut of the desert locust, Schistocerca gregaria, between three different time points after feeding, i.e., 24 h (no active digestion), 10 min (the initial stage of feeding), and 2 h (active food digestion). The observed gene expression profiles were consistent with the polyphagous herbivorous lifestyle of this hemimetabolan (orthopteran) species. Our study reveals the upregulation of 576 genes 2 hours post-feeding. These are mostly predicted to be associated with digestive physiology, such as genes encoding putative digestive enzymes or nutrient transporters, as well as genes putatively involved in immunity or in xenobiotic metabolism. The 10 min time point represented an intermediate condition, suggesting that the S. gregaria midgut can react rapidly at the transcriptional level to the presence of food. Additionally, our study demonstrated the critical importance of two transcripts that exhibited a significant upregulation 2 hours post-feeding: the vacuolar H+ V-ATPase subunit-a and the sterol transporter Niemann-Pick 1b protein, which upon RNAi-induced knockdown resulted in a marked increase in mortality. Their vital role and accessibility via the midgut lumen may make the encoded proteins promising insecticidal target candidates, considering that the desert locust is infamous for its huge migrating swarms that can devastate the agricultural production in large areas of Northern Africa, the Middle East, and South Asia. In conclusion, the transcriptome datasets presented here will provide a useful and promising resource for studying the midgut physiology of S. gregaria, a socio-economically important pest species.